Influence of psychophysical preparation in school of childbirth on the course of pregnancy and delivery - Piziak, Weronika (European Journal of Clinical and Experimental Medicine, 2009)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Introduction: The school of childbirth is a refresher and preparatory course to delivery and maternity. The main task of childbirth school is health promotion and delivery psychoprevention. In the paper, there the results of the research assessing the influence of psychophysical preparation in school of childbirth on the course of a pregnancy and delivery have been discussed. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The Aim: The aim of the study was to assess to what degree participation in school of childbirth influences pregnancy and delivery. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The Material and the Method: The research included 101 women who gave birth, between 25 and 41 years of age. The participation in childbirth preparation courses was the main criterion according to which the group of women was divided in to research group (54 women) and control group (47 women). In the research process, anonymous personal questionnaires were filled. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The Results: The pregnancy mood was closely related to the level of knowledge. Most of the examined women ate in a rational manner and avoided stimulants. Participants of childbirth school twice more often delivered vaginally and knew very well the methods to alleviate pain and were able to use those methods. 88,9% of the research group think that they have been prepared to delivery well or very well, whereas only 42,18 of the control group think the same. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Conclusion: On the basis of the results of the research, it is easy to see the difference in preparation to pregnancy and delivery between participants and non-participants of the school of childbirth. The didactic actions in the school of childbirth can significantly improve the course of pregnancy and delivery.